PENGARUH VARIETAS DAN PENGOLAHAN TANAH TERHADAP PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis Hipogaea.L) - Muhamad Amin Putra; Yekti Maryani; Darnawi (JURNAL ILMIAH AGROUST, 2025)
This study aims to determine the effect of variety and soil treatment on the growth and yield of peanuts (Arachis Hypogaea L.). The study was conducted from July to November 2024 at the self-help agricultural and rural training center (P4S) “Lestari Makmur” on Jalan Wates km 12, Dusun Poleman, Argorejo, Sedayu District, Bantul Regency, DIY. The agronomic characteristics of the study site include a lowland area with an elevation of 88 meters above sea level (masl), soil pH ranging from 5.5 to 6.7, temperature between 26 and 32°C, and annual rainfall of 1,564 mm. This study was designed as a Complete Randomized Block Design with three replications, consisting of Varieties (V) comprising three types: V1 (Giraffe), V2 (Elephant), and V3 (Kancil), and Soil Preparation (T) consisting of three types: T1 (Soil Preparation), T2 (No Soil Preparation), and T3 (Soil Preparation + Straw). The observed variables included: plant height (cm), number of leaves, fresh plant weight, dry plant weight, number of pods per plant, number of filled pods per plant, pod weight per plant, fresh pod weight per harvest plot, and seed weight per plot. Analysis was conducted using a 5% analysis of variance (ANOVA). If significant differences were found, the analysis was continued with Duncan’s Multiple Range Test (DMRT) at the 5% level. The results of the variety treatment and soil cultivation showed no interaction on the growth and yield of peanut plants, the variety treatment showed no significant difference on the growth and yield of peanut plants except for the number of leaves, the soil cultivation treatment showed no significant difference on the growth and yield of peanut plants except for the number of pods per plant.